Shylock in Fuquieo: Shakespeare’s The Merchant of Venice and the Trial of a Portuguese Stranger by China’s Courts in Richard Hakluyt’s Principal Navigations - Hokama, Rhema Mei Lan (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
In 1548, the Portuguese merchant Galeotto Perera was captured along with his shipmates in the waters off China’s southeastern coast. In his account of his time as a prisoner in Fuquieo (in contemporary Fujian province), Perera details his trial before the city’s magistrates in a Chinese court of law, writing of his amazement when he and his fellow Portuguese merchants were acquitted of the charges brought against them by two of the city’s most prominent men. Perera’s prison account reached an Elizabethan readership via Richard Hakluyt’s Principal Navigations (1589), a sprawling compendium of European travel writing translated into English. In this essay, I maintain that the outcome of Shylock’s trial in Shakespeare’s comedy entails a reversal of Perera’s legal fortunes in China. In light of Perera’s assertion that the Chinese legal process “cannot be falsified, as it happeneth sometimes with vs,” I argue that The Merchant of Venice asks why these European failures of justice, mercy, and truth sometimes happen in Europe’s courts and in negotiations with non-Christian peoples. I aim to demonstrate that the comedy’s treatment of economic and religious exchange with strangers is inflected by Perera’s account of his encounters with the Chinese during his time in Fuquieo—as well as by other travel writings collected by Hakluyt that describe legal, financial, and inheritance quandaries that European traders faced during their travels to places like China, Java, and modern-day Myanmar.